Role of CT-guided transthoracic biopsy in the diagnosis of mycobacterial infection. (11th January 2019) - Beck, Kyongmin Sarah; Han, Dae Hee; Lee, Kyo Young; Kim, Seung Joon
Abstract : Mycobacterial infection(MI) is sometimes diagnosed using CT-guided transthoracic needle biopsy (TNB). However, the exact role of CT-guided TNB in this diagnostic process is not clearly known. The purpose of this study is to analyze the role of CT-guided TNB in patients with MI who present with a focal lung lesion. Of 1233 patients who underwent CT-guided TNB from January 2010 through February 2016 at our institution, patients with a final diagnosis of MI were included for analysis. Clinical characteristics and biopsy-related factors were compared between patients whose diagnosis could be established using TNB samples alone (group 1) and those whose samples from additional tests were necessary for diagnosis (group 2). We also analyzed the possible benefit of CT-guided TNB as compared with bronchoscopy in a subgroup who underwent both procedures. 47 patients with MI were included in the study, with 37 patients (78.7%) in group 1 and 10 patients (21.2%) in group 2. There was no statistically significant difference in clinical characteristics or biopsy-related factors between the two groups. Of 41 patients with MI who underwent both bronchoscopy and TNB, success in diagnosis was solely attributable to TNB in 16 (39.0%) patients; in 19 (46.0%) patients, diagnosis could be made based on bronchoscopy results alone. MI can be successfully diagnosed by CT-guided TNB in about 80% of patients with MI who underwent TNB, but 46% of the patients could have been diagnosed with bronchoscopy results alone. CT-guided TNB is inferior to bronchoscopy in the differentiation of Mycobacterium species even in peripheral lung lesions.